Comparison of Fundus-Guided Microperimetry and Multifocal Electroretinography for Evaluating Hydroxychloroquine Maculopathy - Alghanem, Husam (Transl Vis Sci Technol, 2019)
PURPOSE: To compare retinal function by using fundus-guided microperimetry (MP) and multifocal electroretinography (mfERG) for detecting hydroxychloroquine (HCQ) maculopathy. METHODS: Forty-six eyes of 25 patients referred to our clinical practice for HCQ maculopathy assessment and 3 groups of normal control subjects were evaluated by mfERG and MP. Macular structure was assessed using spectral-domain optical coherence tomography (SD-OCT). Ring ratios from the three innermost mERG rings were compared with average sensitivity of each MP ring at approximately equivalent distances from the fovea. HCQ toxicity was defined as an mfERG ring ratio or mean MP ring sensitivity >2 standard deviations below the normal mean. The sensitivity and specificity of MP to detect HCQ toxicity relative to mfERG were evaluated. RESULTS: MP rings MR2 and MR3 were positively correlated with corresponding mfERG ring ratios (r = 0.52, P = 0.002 and r = 0.56, P < 0.001 respectively). Ring 2 and ring 3 measures of MP and mfERG were significantly worse in HCQ eyes than controls (P < 0.001). The sensitivity of MP to detect toxicity for MR1 through MR3 ranged from 33% to 88%, whereas specificity ranged from 72% to 85%. Through rings 1 to 3, the frequency of abnormal function ranged from 20% to 48% for MP, 11% to 35% for mfERG, and 41% to 45% for SD-OCT. CONCLUSIONS: The frequency of detection of HCQ toxicity with MP was greater than with mfERG. MP showed an overall good sensitivity and moderate specificity in detecting HCQ-induced functional deficits. TRANSLATIONAL RELEVANCE: Results from this study may allow clinicians to improve screening accuracy for HCQ toxicity by using the alternative modality of MP.